Heterogeneous SnO2/ZnO nanoparticulate film: Facile synthesis and humidity sensing capability. (July 2018) - Ismail, A.S.; Mamat, M.H.; Malek, M.F.; Yusoff, M.M.; Mohamed, R.; Sin, N.D. Md.; Suriani, A.B.; Rusop, M.
Abstract: Highly sensitive and extremely thin tin oxide/zinc oxide (SnO2 /ZnO) heterojunction films were prepared via a two-step solution-based method for humidity-sensing application. The average diameters of the ZnO and SnO2 nanoparticles were 26 and 6 nm, respectively. The deposition of SnO2 for 3 min reduced film resistance from 6.74 MΩ to 0.40 MΩ. Remarkably, the humidity-sensing performance of the heterojunction sensors was critically dependent on deposition time, and sensors subjected to 3 min deposition exhibited the highest sensitivity (90.56) to humidity, which was significantly higher than that of bare ZnO. This study indicates that the use of SnO2 /ZnO heterojunction has a great potential in humidity sensing applications.